Application of Human Rights Principles in the Formation of Draft Laws Concerning the Civil Code - Muljono, Bambang Eko; Rochmawanto, Munif; Tjahjani, Joejoen (Jurnal Independent, 2023)
Abstract As a rule of law, Indonesia has an obligation to guarantee people's welfare through law. Good legislation is legislation that has a basis or foundation called Grundnorm. Grundnorm is a foundation for forming laws that have the value of justice. Apart from that, good laws and regulations must fulfill principles and concepts, protect human rights, and must pay attention to community participation. Because the purpose of forming laws and regulations is to protect the public. This research aims to find out how good legislation is formed and how the community participates in implementing the formation of legislation. In forming laws and regulations, various aspects must be taken into account. This is so that the aim of forming legislation can be achieved and does not injure the rights of the Indonesian people. The formation of laws and regulations must be democratic, aspirational and participatory. Standard Norms and Regulations (SNP) on Human Rights is a document which is an implementable explanation of various human rights instruments, both international and national, as well as human rights norms which continue to develop dynamically, to suit the context and events, especially in Indonesia. Standard Norms and Regulations regarding the Right to Obtain Justice are expected to become references and guidelines in carrying out discussions and amendments to the Draft Criminal Code.